ORGANIZATIONAL AND MANAGERIAL FACTORS INFLUENCING ELECTRONIC HEALTH RECORDS IMPLEMENTATION IN PUBLIC HEALTH FACILITIES, MACHAKOS COUNTY, KENYA - Violet Chepchirchir Maritim; Margaret Wandera Nyongesa; Julius Ndung'u (International Journal of Health Services Research and Policy)
The adoption of Electronic Health Records (EHRs) in healthcare systems has the potential to improve patient care, reduce turnaround times, and leverage secondary data for enhanced decision-making. Information technologies are increasingly being embraced in healthcare to promote accountability, efficiency, and service delivery. This study aimed to identify managerial and organizational factors influencing the implementation of EHRs in public health facilities in Machakos County, Kenya. A cross-sectional descriptive design was adopted, as it allows for the collection of data at a single point in time across a diverse population, making it suitable for identifying prevalent factors influencing EHR adoption without requiring longitudinal follow-up. The target population consisted of 424 healthcare providers, including management officers, ICT officers, and healthcare workers. Purposive sampling was used to select key informants with specific knowledge on EHR implementation, ensuring depth and relevance in qualitative insights. Stratified random sampling was applied to the broader population of healthcare providers to ensure representation across different cadres and facility levels, which enhances the generalizability of the findings. The combination of these sampling techniques helps reduce selection bias by ensuring both inclusivity and relevance. A total of 411 respondents were reached. Additionally, qualitative data were collected through interviews with eight key informants. Quantitative data were analyzed using SPSS, while NVivo was used for qualitative analysis. Chi-square tests were applied to determine statistical significance. The results indicated that adequate hardware and software infrastructure, ICT literacy, resource availability, capacity building, and strong leadership commitment were significant factors influencing successful EHR adoption. The study concluded that both organizational and managerial factors must be addressed to ensure effective EHR implementation. It recommends investment in infrastructure, capacity building, and leadership commitment as essential for EHR systems to improve patient outcomes and enhance operational efficiency.